(untitled) (Bangladesh Journal of Botany, 2022)
Thirty-five accessions of bird’s eye chilli (Capsicum frutescens L.) were evaluated for genetic variability, diversity and character association between various traits. Analysis of variance revealed high significant differences among all the accessions for all the characters studied. High to moderate estimates of genotypic coefficient of variation and phenotypic coefficient of variation were reported for most of the characters studied indicating the presence of wide variability among the accessions. Correlation studies indicated positive association of fruit yield per plant with weight of seeds per fruit, fresh weight of ten fruits and fruit length. Out of 19 characters studied, 16 showed direct positive effect on yield per plant. Accessions were grouped into six clusters with inter cluster D2 values ranging between 172.33 and 1275.15. Higher ascorbic acid and capsaicin contents were recorded in Acc.133 and Acc.164, respectively. The most promising accessions for fruit yield were Acc.160 and Acc.158. Bangladesh J. Bot. 51(1): 9-16, 2022 (March)